A conserved immunogenic and vulnerable site on the coronavirus spike protein delineated by cross-reactive monoclonal antibodies - Chunyan Wang (Nature Portfolio, 2021)
Here, the authors report the isolation and characterization of two human monoclonal antibodies (mAbs) from immunized mice with trimeric spike ectodomains of three human betacoronaviruses HCoV-OC43, SARS-CoV and MERSCoV, and show that while exhibiting cross-reactivity, the mAbs only neutralize MERS-CoV but not SARS-CoV nor SARS-CoV-2, likely due to the subtle epitope differences in the spike S2 fusion subunit.